Metaverse Adoption in Public Sector: A Bibliometric Analysis - Mailangkay, Adele; Napitupulu, Darmawan (Universitas Muhammadiyah Malang, 2024)
The objective of this study is to map the landscape and knowledge structure of the public sector metaverse through bibliometric analysis. Following this, a descriptive overview of the current state of public sector research related to the metaverse, including the leading ten authors and sources, most relevant keywords, and primary research topics, will be presented. The selection of the Scopus database was based on its status as the largest repository of its kind and its provision of an extensive compilation of abstracts and citations for peer-reviewed articles, proceedings, and journals. The initial search yielded 369 documents from Scopus; after eliminating duplicate and irrelevant articles, 354 documents remained. The results demonstrate the substantial development of the metaverse in the public sector, with an annual growth rate of 14.89%. This indicates that the adoption of virtual technology and the metaverse is gaining importance in the public sector. Castronova ranks first in terms of the quantity of studies published, with five articles, followed by De Kool and Zhang.